PENGARUH KEADILAN, KETEPATAN PENGALOKASIAN, TEKNOLOGI SISTEM PERPAJAKAN TERHADAP KECENDERUNGAN MELAKUKAN PENGGELAPAN PAJAK (TAX EVASION) (Studi di Wilayah KPP Pratama Semarang Candisari ) (Students' Journal of Accounting and Banking, 2014)
This research aims to know the influence of fairness, appropriateness of the Assignment, the tax system Technology, against the tendency of Tax Evasion (Tax Evasion), according to the perception of the Taxpayer.The population of this research is the area South of Semarang KPP. The sample in this research in the specify calculation based on slovin formula and sample selection Technique using probability Sampling with Sample random sampling because it populations is done at random without regard to existing strata in the population and members of the population are considered homogeneous. Research methods of analysis used was multiple linear regression.Based on the results of hypothesis shows that justice is a negative and significant effect on the tendency to make Tax Evasion. Accuracy of allocating and technology tax system affect the negative and not significant to the tendency of Tax Evasion did then the statement was denied.Keywords: Fairness, Accuracy Of Allocating, Technology Tax System, Tax Evasion, Tax Payers Perception